Multiparameter optical diagnostics for high-speed flow applications - Chakravarthy, K (2021)
This thesis details the development of two multiparameter spatially-resolved optical diagnostic techniques for research in high-speed flow applications. This is motivated by the need to extract as much information as possible in physics-coupled, multidimensional flows, and flows generated in short duration test facilities.